Female director appointments under institutional change: Neutralizing response to competing logics - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2020)
We examine female board appointments in Japan to investigate how managers respond to conflicting institutional logics: all-male insider control vs. gender diversity. Using fuzzy-set qualitative comparative analysis (fsQCA), we find that female board appointments occur when several factors combine to put pressure on firms: stock market underperformance, high levels of visibility, the absence of a stabilizing family owner, and various configurations of foreign shareholder and outside director power as well as the absence of prior female board appointments. However, most firms appoint women with an internal orientation, i.e., who see themselves as working for insiders rather than outside stakeholders such as shareholders. Firms thus adopt the new logics while simultaneously neutralizing its impact. This suggests a possible extension of theory on resolving conflicting institutional logics. We further contribute to our understanding of the international diffusion of corporate governance processes.